Study of Spleen and Liver Injuries in Patients of Blunt Trauma Abdomen - Abdul Latif, Muhammad Alim, Bahadur Khan, Khaleel Ahmad Khan, Jeevan Kumar (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To study the spleen and liver injuries in patients of blunt trauma abdomen. Material and methods: This was a cross sectional study which conducted at Department of Surgery Loralai Medical College Loralai from May 2021 to November 2021 over the period of 6 months. Total 130 patients aged 18-50 years either gender with blunt trauma abdomen were recruited for this study. Spleen and liver injuries and their grading was studied. Results: Total 130 patients of blunt abdominal trauma were recruited. Age range was 18-50 years with mean age 30.85 ± 8.84 years. Out of 130 patients, liver injury was found in 67 (52%) patients. Total 84 (65%) patients had spleen injury. Total 20 (15%) patients had both liver and spleen injury. Conclusion: Results of this study concluded that spleen was the most common injured organ. Grade-I liver and spleen injury was commonly seen. Age group 18-33 years was common age group and males were prominent than females.